Metaphorical Adjectives Describing Human in Javanese - Nuryantiningsih, Farida; Suhandano, Suhandano; Sulistyawati, Sulistyawati (Jurnal Lingua Idea, 2023)
This study examines metaphorical adjectives describing humans in Javanese. The metaphorical adjective is literally used to describe nouns other than humans but figuratively used to describe humans. This study aims to describe metaphorical adjectives used to characterize humans figuratively based on their meaning type. This study used a descriptive qualitative approach. The data in this study are adjectives used to describe humans in Javanese metaphorically. The data corpus is taken from written and oral sources. The written sources are taken from the Dictionary of Baoesastra Djawa written by Poerwadarminta dan Javanese Dictionary written by the Language Center Team of Yogyakarta and a Javanese short story from the anthology of Javanese literature short story 2007 Kidung Megatruh (22 short stories) and short story of Yogyakarta Javanese in 2000-2010 (87 short stories). Data analysis techniques are inductive, with identification and classification techniques following research objectives. Based on the result, 43 adjectives are used to describe humans with metaphorical meanings. The adjectives are divided into six types: adjectives of positive character marker, negative character marker, positive mental condition marker, negative mental condition marker, positive physical condition marker, and negative physical condition marker. The use of metaphorical adjectives explaining humans in Javanese shows that the creativity of Javanese linguists is good at utilizing existing lexicons to express ideas by distorting their meaning without creating a new lexicon.